Perceptions of Primary Care Among Breast Cancer Survivors: The Effects of Weight Status - Christian, Allison (Health Serv Res Manag Epidemiol, 2015)
BACKGROUND: Obese breast cancer survivors (BCSs) are impacted by diminished quality of life (QOL), multiple comorbid conditions, and poor disease outcomes. Despite national guidelines recommending a healthy weight to improve QOL and outcomes posttreatment, support and education are not routinely provided to BCSs in primary care. To fill this gap, we assessed perceptions of primary care received among BCSs by weight status. METHODS: Cross-sectional surveys were administered to early-stage BCSs (N = 188) from 2 New Jersey cancer centers between May 2012 and July 2013. Sociodemographics, medical history, functional health status, perceived satisfaction with one’s primary care provider (PCP), and PCP involvement in follow-up care were assessed. RESULTS: In total, 82% of overweight BCSs and 30% of obese BCSs reported not being told by their doctor that they were overweight or obese, despite these conditions being highly prevalent (35% and 35%, respectively). Obese BCSs were more likely than healthy weight BCSs to be African American, have a higher comorbidity score, poorer functional health, and greater satisfaction with their PCPs. CONCLUSION: The PCP–patient encounter may represent an opportunity for PCPs to correct misperceptions and promote weight reduction efforts among BCSs, thus improving QOL and disease outcomes.